2021
DOI: 10.1080/15592324.2021.1991687
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate alleviates ammonium toxicity in wheat (Triticum aestivumL.) by regulating tricarboxylic acid cycle and reducing rhizospheric acidification and oxidative damage

Abstract: Ammonium (NH 4 + ) is one of the most important nutrients required by plants. However, a high concentration of NH 4 + as the sole nitrogen source suppresses plant growth. Although nitrate (NO 3 − ) can alleviate NH 4 + toxicity, the mechanisms underlying this ability have not been fully elucidated. In this study, wheat plants were cultivated in hydroponic solution with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 73 publications
3
6
0
Order By: Relevance
“…The authors proposed that medium alkalization by nitrate absorption and assimilation may play a role in ammonium detoxification (Hachiya et al, 2012). This notion is supported by a recent study in wheat that NO 3 − supply can inhibit H + efflux mediated by NH 4 + uptake (Du et al, 2021). Previously, our studies indicated that a NO 3 − efflux channel SLAH3 is involved in nitrate-dependent alleviation of ammonium toxicity and, importantly, the medium alkalization greatly contributes to this process (Zheng et al, 2015;Sun et al, 2021).…”
Section: Introductionsupporting
confidence: 63%
“…The authors proposed that medium alkalization by nitrate absorption and assimilation may play a role in ammonium detoxification (Hachiya et al, 2012). This notion is supported by a recent study in wheat that NO 3 − supply can inhibit H + efflux mediated by NH 4 + uptake (Du et al, 2021). Previously, our studies indicated that a NO 3 − efflux channel SLAH3 is involved in nitrate-dependent alleviation of ammonium toxicity and, importantly, the medium alkalization greatly contributes to this process (Zheng et al, 2015;Sun et al, 2021).…”
Section: Introductionsupporting
confidence: 63%
“…In contrast to NRT‐mediated NO3 uptake, which is typically associated with H + influx, NH4+ uptake via AMTs is driven by the electrical potential generated by PM H + ‐ATPase to maintain charge balance (Meier et al., 2020; Vidal et al., 2020; Xu et al., 2012). NO3 may assist in dissipate H + efflux caused by NH4+ uptake, which can lead to rhizosphere alkalization and alleviate NH4+ toxicity (Du et al., 2021; Xiao et al., 2022). In Arabidopsis , SLAH3, a NO3 permeable channel, facilitates NO3 efflux from the root and participates in NO3‐dependent mitigation of NH4+ toxicity (Zheng et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A small amount of NO 3 − is able to effectively alleviate NH 4 + toxicity in many plant species such as maize, wheat, tomato, cucumber, and Arabidopsis , referred to as NO 3 − ‐dependent alleviation of NH 4 + toxicity (Roosta and Schjoerring, 2008; Garnica et al, 2010; Hachiya et al, 2012; Du et al, 2021). Although NO 3 − ‐based N fertilizers have been used to antagonize NH 4 + toxicity in agricultural practice for a long time, how NO 3 − detoxifies NH 4 + has been blurred until very recently (Hachiya et al, 2012).…”
Section: Nitrate‐dependent Alleviation Of Nh4+ Toxicitymentioning
confidence: 99%
“…Nitrate, however, was found to relieve NH 4 + toxicity without affecting NH 4 + accumulation, organic acids, and inorganic cations (Hachiya et al, 2012). Instead, several studies in wheat, cucumber, and Arabidopsis (Wang et al, 2004; Roosta and Schjoerring, 2007; Du et al, 2021) have shown that NO 3 − supply can accelerate NH 4 + assimilation, promote organic acid synthesis in the TCA cycle, and maintain inorganic cation levels. In addition, NO 3 − may function as a signaling molecule to modulate the signal pathways of hormones such as CK and IAA, as either low or high levels of NO 3 − are sufficient to alter hormone levels under high‐NH 4 + conditions (Garnica et al, 2010).…”
Section: Nitrate‐dependent Alleviation Of Nh4+ Toxicitymentioning
confidence: 99%
See 1 more Smart Citation